Lessons from the renewal of the National Cervical Screening Program in Australia - Megan Smith; Ian Hammond; Marion Saville (Sax Institute, 2019)
Objectives: Australia was one of the first countries to make the transition from cytology-based to HPV-based cervical screening.This analysis of the national program's transition to a new model looks at the lessons learnt that can provide valuable insights to other settings. Type of program: Australia's National Cervical Screening Program (NCSP). Methods: Following an extensive policy review, in December 2017 the NCSP transitioned from 2-yearly cytology-based screening in women from age 18, to 5-yearly primary HPV screening from age 25. Results: Some changes were more complex than initially anticipated. Building and implementing the National Cancer Screening Register was a more demanding and specialised project than expected. Regulatory requirements for self-collection were unexpectedly onerous, because self-collection was not formally included as an intended use by HPV test manufacturers. This delayed the rollout of a key measure to improve participation and equity. Colposcopy demand was expected to increase substantially but exceeded expectations. Uncertainty about appropriate clinical management or testing outside guideline recommendations may have contributed to the excess demand, highlighting the importance of training providers in the rationale for guidelines as well as the content. Lessons learnt: Although the changes were evidence based, there were nevertheless some concerns among women and healthcare providers, especially about the longer interval and later starting age for screening. These could have been reduced through earlier and more extensively delivered information to healthcare providers, who play a key role in addressing community concerns. Improved coordination of stakeholder support between government and nongovernment organisations may also have extended both the reach and credibility of communication about the program changes. Transitioning a well-established program is challenging, not only because of the changes required, but also because the existing program must continue to function until the transition. Delays may be hard to avoid, but early communication will enable better forward planning, especially by service providers. Since delays can reduce wider confidence in the changes, proactive communication is critical. Achieving high and equitable screening coverage is a key element if Australia and other countries are to succeed in eliminating cervical cancer as a public health problem. Improving screening program confidence and participation remain important ongoing work. Lessons from Australia will provide valuable insights for other countries making similar changes.